Twist and return-induced ring strain triggers quick relaxation of a (Z)-stabilized cyclobisazobenzene - Slavov, Chavdar; Yang, Chong; Heindl, Andreas H.; Neudecker, Tim; Wegner, Hermann A.; Dreuw, Andreas; Wachtveitl, Josef (The journal of physical chemistry letters, 2018)
Continuous irradiation of the thermodynamically stable (Z,Z)-cyclobisazobenzene does not lead to accumulation of a (Z,E) or (E,E) isomer as one might expect. Our combined experimental and computational investigation reveals that Z → E photoisomerization still takes place on an ultrafast time scale but induces large ring strain in the macrocycle, which leads to a very fast thermal back-isomerization, preventing photostationary accumulation of (E)-isomers
Gesehen am 07.06.2019